Novel CNS malformations and skeletal anomalies in a patient with Beaulieu‐boycott‐Innes syndrome. Issue 12 (20th September 2018) - Accogli, Andrea; Scala, Marcello; Calcagno, Annalisa; Castello, Raffaele; Torella, Annalaura; Musacchia, Francesco; Allegri, Anna M. E.; Mancardi, Maria M.; Maghnie, Mohamad; Severino, Mariasavina; ,; Nigro, Vincenzo; et al.
Abstract : THO/TREX (transcription/export) is a conserved eukaryotic complex that plays a crucial role in gene expression and prevents DNA damage during mitosis and meiosis. In mammals, TREX is essential during embryogenesis, determining stem cell fate specification by regulating posttranscriptional self‐renewal and differentiation in several tissues. It is composed of a core called THO, consisting of THOC1, 2, 5, 6, 7, and additional proteins. Bi‐allelic mutations in THOC6 have been associated to Beaulieu–Boycott–Innes syndrome (BBIS), a syndromic form of intellectual disability (ID). To date, nine patients harbouring homozygous or compound heterozygous mutations in THOC6 have been reported. Despite the clinical heterogenity and subtle dysmorphic features in some individuals, distinctive facial features are tall forehead, short and upslanting palpebral fissures, deep set eyes, flat philtrum, and malocclusion. Nonlife threatening congenital anomalies are common, including cardiac and renal malformations, anteriorly displaced anus, cryptorchidism in males, submucous cleft palate, and corpus callosum dysgenesis. Affected patients usually have short stature, mild microcephaly, and mild to moderate ID. Here, we describe an Italian patient with BBIS, carrying two compound heterozygous loss‐of‐function (LoF) variants in THOC6 (c.577C > T, p.R193* and c.792_793delCA, p.V264Vfs*48). In addition to the common phenotype, she displays cerebellar hypoplasia with severe vermian dysgenesis and hydrocephalus due to aqueductal stenosis, multiple skeletal anomalies and hypergonadotropic hypogonadism. Thus, we review the previous cases and discuss the phenotypic spectrum of BBIS, providing further evidence regarding the pivotal role of TREX complex in human development.